2023
DOI: 10.32388/3qzj1r
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Forecasting by Analogy: A Parallel between the Trend of Confirmed COVID-19 Deaths in the Winters of 2022/2023 and 2023/2024 in Italy

Marco Roccetti

Abstract: We studied the weekly number and the growth/decline rates of COVID-19 deaths in the period October 31, 2022 – February 9, 2023, in Italy, finding that that COVID-19 winter wave reached its peak during the three holyday weeks extending from December 16, 2022 to January 5, 2023, and it was definitely trending downward, returning to the same number of deaths of the end of October 2022, in the week February 3 – 9, 2023. During this period of fifteen weeks, that wave caused a number of deaths as large as 8,526. Its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, recent studies [39,40] indicate that the death cases reported in the official data of the Protezione Civile department (DPC) [38] are underestimated. Considering excess mortality computed using data provided by the National Statistical Institute (ISTAT) by subtracting the average deaths counted in February-April over the prior 5 years (2015-2019) from the deaths counted in the same period in 2020 [29], the results are similar.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent studies [39,40] indicate that the death cases reported in the official data of the Protezione Civile department (DPC) [38] are underestimated. Considering excess mortality computed using data provided by the National Statistical Institute (ISTAT) by subtracting the average deaths counted in February-April over the prior 5 years (2015-2019) from the deaths counted in the same period in 2020 [29], the results are similar.…”
Section: Resultsmentioning
confidence: 99%